Label free urea biosensor based on organic electrochemical transistors. (14th June 2018) - Berto, Marcello; Diacci, Chiara; Theuer, Lorenz; Di Lauro, Michele; Simon, Daniel T; Berggren, Magnus; Biscarini, Fabio; Beni, Valerio; Bortolotti, Carlo A
Abstract: The quantification of urea is of the utmost importance not only in medical diagnosis, where it serves as a potential indicator of kidney and liver disfunction, but also in food safety and environmental control. Here, we describe a urea biosensor based on urease entrapped in a crosslinked gelatin hydrogel, deposited onto a fully printed PEDOT:PSS-based organic electrochemical transistor (OECT). The device response is based on the modulation of the channel conductivity by the ionic species produced upon urea hydrolysis catalyzed by the entrapped urease. The biosensor shows excellent reproducibility, a limit of detection as low as 1 μ M and a response time of a few minutes. The fabrication of the OECTs by screen-printing on flexible substrates ensures a significant reduction in manufacturing time and costs. The low dimensionality and operational voltages (0.5 V or below) of these devices contribute to make these enzymatic OECT-based biosensors as appealing candidates for high-throughput monitoring of urea levels at the point-of-care or in the field.